2011
DOI: 10.1007/s00705-011-1204-8
|View full text |Cite
|
Sign up to set email alerts
|

Human metapneumovirus strains circulating in Latin America

Abstract: The human metapneumovirus (HMPV) is responsible for acute respiratory tract infections in young children, elderly patients, and immunocompromised hosts. In this study, we genetically analyzed the circulating HMPV in Central and South America from July 2008 to June 2009 and characterized the strains present in this region. Samples were collected during an international collaborative influenza like illness surveillance study and then sequenced with specific primers for the HMPV G gene. Our results show that two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
3
11
0
1
Order By: Relevance
“…However, the circulation of other genotypes cannot be rule out, and further studies are needed to analyze the strains that could be circulating in an outbreak from mild moderate and severe ALRI cases. The preponderance of genotype A2 over genotype B2 in 2009 and 2010 and the circulation of genotype A2 in 2011 only, in agreement with previous studies such as those reported by Li et al in China and García et al in Peru [7], [30], suggest that genotype A2 has higher fitness than genotype B2. This hypothesis could be supported by higher values of effective population size and genetic distance of A2 over B2.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the circulation of other genotypes cannot be rule out, and further studies are needed to analyze the strains that could be circulating in an outbreak from mild moderate and severe ALRI cases. The preponderance of genotype A2 over genotype B2 in 2009 and 2010 and the circulation of genotype A2 in 2011 only, in agreement with previous studies such as those reported by Li et al in China and García et al in Peru [7], [30], suggest that genotype A2 has higher fitness than genotype B2. This hypothesis could be supported by higher values of effective population size and genetic distance of A2 over B2.…”
Section: Discussionsupporting
confidence: 91%
“…The phylogenetic analyses showed cocirculation of genotypes A2 and B2, as was reported in other Latin American countries such as Peru, and Brazil [29], [30]. However, in contrast with previous reports [31], we found no changes in dominance of one group over the other (A and B), but the preponderance of genotype A2 during the study period.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies have demonstrated that ILI activity peaks in winter in Lima, but is less seasonal in Piura and Iquitos, which tend to have year‐round incidence (Y.Tinoco unpublished data). The field and laboratory methods of the surveillance studies yielding this biobank of HMPV‐positive specimens from these three cities are described in full detail elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…6 (NAMRU‐6) in Callao, Peru, where they underwent initial screening for a broad number of respiratory viruses using Madin‐Darby canine kidney (MDCK), African green monkey kidney (Vero76 and VeroE6), and Rhesus monkey kidney (LLCMK2) cell lines. Upon demonstration of cytopathic effect, respiratory virus identification was performed by direct immunofluorescence (D3 DFA Respiratory Virus Diagnostic Hybrids; Athens, OH), for adenoviruses, influenza A virus, influenza B virus, parainfluenza viruses, respiratory syncytial respiratory viruses, and HMPV . Those specimens positive for HMPV by immunofluorescence then underwent confirmatory testing by PCR as described by Garcia et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation